2012
DOI: 10.1002/glia.22429
|View full text |Cite
|
Sign up to set email alerts
|

Cell death and neuronal differentiation of glioblastoma stem‐like cells induced by neurogenic transcription factors

Abstract: Glioblastoma multiform (GBM) are devastating brain tumors containing a fraction of multipotent stem-like cells which are highly tumorigenic. These cells are resistant to treatments and are likely to be responsible for tumor recurrence. One approach to eliminate GBM stem-like cells would be to force their terminal differentiation. During development, neurons formation is controlled by neurogenic transcription factors such as Ngn1/2 and NeuroD1. We found that in comparison with oligodendrogenic genes, the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 41 publications
5
88
0
Order By: Relevance
“…We also found that transient expression of Ngn2 (by a non-donor episomal plasmid) in radial glia was sufficient to produce ATRT like tumors. The effectiveness of transient Ngn2 expression, in combination with previous findings that Ngn2 or NeuroD1 expressed in glioma cells induces cell death and neuronal differentiation without changing tumor type (46, 47) supports the idea that Ngn2 and NeuroD1 acts in early stage radial progenitors to change the type of tumor generated. We have co-expressed Ngn2 with GFAP donor plasmids and found the resulted tumors were similar to tumors induced by GFAP donor plasmids alone.…”
Section: Discussionsupporting
confidence: 80%
“…We also found that transient expression of Ngn2 (by a non-donor episomal plasmid) in radial glia was sufficient to produce ATRT like tumors. The effectiveness of transient Ngn2 expression, in combination with previous findings that Ngn2 or NeuroD1 expressed in glioma cells induces cell death and neuronal differentiation without changing tumor type (46, 47) supports the idea that Ngn2 and NeuroD1 acts in early stage radial progenitors to change the type of tumor generated. We have co-expressed Ngn2 with GFAP donor plasmids and found the resulted tumors were similar to tumors induced by GFAP donor plasmids alone.…”
Section: Discussionsupporting
confidence: 80%
“…This approach is based on the concept that cancer cells arise from tissue stem cells and share the stemness and plasticity with normal stem cells. Differentiation therapy aims to induce cancer cells to differentiate by treatment with differentiation-inducing agents [46,47]. Most of the differentiation agents can inhibit proliferation and induce cells to differentiate and then undergo apoptosis [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…27 SNB 75 displays prominent mesenchymal features, 28 while Gli4 and Gli7 express proneural characteristics. 18 However, both 5.3d and 3.2a (data not shown) inhibit Gli4 and GLi7 invasion capacity with the same efficiency.…”
Section: Discussionmentioning
confidence: 82%